Substance use disorders and COVID-19: reflections on international research and practice changes during the “poly-crisis” - Carver, Hannah; Ciolompea, Teodora; Conway, Anna; Kilian, Carolin; McDonald, Rebecca; Meksi, Andia; Wojnar, Marcin (Frontiers in Public Health, 2023)
Since its official onset in March 2020, the COVID-19 pandemic has had a disproportionately high toll on vulnerable populations, coinciding with an increased in the prevalence of alcohol-and drugrelated deaths worldwide ands well as pre-existing societal issues such as rising income inequality and homelessness. This poly-crisis has posed unique challenges to service delivery for public health services, healthcare providers, and low threshold services for people with substance use disorders, and a range of innovative approaches have emerged. In this Perspectives paper we reflect on the poly-crisis and the changes made to research and practice for those experiencing substance use disorders, following work undertaken as part of the InterGLAM project (part of the 2022 . InterGLAM is a European Commission-funded project which co-produced a thematic track on 'Global perspectives on addictions and drug markets' as part of the 4 th European Conference on Addictive Behaviours and Dependencies ("Lisbon Addictions") conference) in November 2022. The authors, who were part of an InterGLAM working group, whose focus was the poly-crisis, and we have identified a range of creative and novel responses by gathering information from conference attendees about COVID-19-related changes to substance use disorder treatment in their countries. In this paper we describe these responses across a range of countries (including but not limited to